2009
DOI: 10.4103/0972-2327.56314
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of typical circle of Willis and the variation in the anterior communicating artery: A study of a Sri Lankan population

Abstract: Objective:To determine the extent of hypoplasia of the component vessels of the circle of Willis (CW) and the anatomical variations in the anterior communicating artery (AcomA) in the subjects who have died of causes unrelated to the brain and compare with previous autopsy studies.Materials and Methods:The external diameter of all the arteries forming the CW in 225 normal Sri Lankan adult cadaver brains was measured using a calibrated grid to determine the occurrence of “typical” CWs, where all of the componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Fetal or embryonic configuration diameter of the P1 is smaller than diameter of P Com A and P2. [ 9 ] In previous studies, the prevalence of a complete anterior circle varied from 74 to 90% in different ethnic groups,[ 9 35 36 37 ] almost similar to our observation. Autopsy studies, however, showed lower incidence of complete circles.…”
Section: Discussionsupporting
confidence: 91%
“…Fetal or embryonic configuration diameter of the P1 is smaller than diameter of P Com A and P2. [ 9 ] In previous studies, the prevalence of a complete anterior circle varied from 74 to 90% in different ethnic groups,[ 9 35 36 37 ] almost similar to our observation. Autopsy studies, however, showed lower incidence of complete circles.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of ACA-A1 of one side is present in 5.6% or 29 examined cases, almost proportionally in women 6.75% and in male 4.8% comparing to 4% [7], 4.76% [9] and 5% [2]. Median ACA is presented in 11 examined patients or 2.1%, in women 2.4% and in men 1.8%, similar results are 2.5% and 5%…”
Section: Discussionsupporting
confidence: 53%
“…Variations in cerebral arteries, particularly in the interhemispheric anterior communicating artery (De Silva et al. ), posterior cerebral arteries, middle cerebral arteries (Gunnal et al. ), bilateral PComA (Chuang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior portion of the cerebral arterial network, the circulus arteriosus cerebri (CAC), first described by a Paduan anatomist Julius Casserius (1552–1616) and subsequently by Thomas Willis (1621–1675), includes the cerebral parts of right and left internal carotid arteries (ICA), pre‐communicating parts of right and left anterior cerebral arteries (ACA), anterior communicating artery (AComA), right and left posterior communicating arteries (PComA), and the pre‐communicating parts of the bilateral posterior cerebral arteries (PCA) (Rogers, ; Feindel, ; De Silva et al. ; Bender et al. ; Vasović et al.…”
Section: Introductionmentioning
confidence: 99%